2022
DOI: 10.1101/2022.06.24.497508
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The slowly evolving genome of the xenacoelomorph wormXenoturbella bocki

Abstract: The evolutionary origins of Bilateria remain enigmatic. One of the more enduring proposals highlights similarities between a cnidarian-like planula larva and simple acoel-like flatworms. This idea is based in part on the view of the Xenacoelomorpha as an outgroup to all other bilaterians which are themselves designated the Nephrozoa (protostomes and deuterostomes). Genome data, which can help to elucidate phylogenetic relationships and provide important comparative data, remain sparse for early branching bilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 112 publications
(228 reference statements)
1
14
0
Order By: Relevance
“…The GC content of this genome amounts to 36.7% (Table 2), so S. roscoffensis can be considered as having an AT-rich genetic makeup. The composition fits well in the range observed for other xenacolomorphs (43% GC content in X. bocki (Schiffer et al 2022), or 39.1% GC content in P. naikaiensis (Arimoto et al 2019); all of them, also, enriched in A+T nucleotides.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The GC content of this genome amounts to 36.7% (Table 2), so S. roscoffensis can be considered as having an AT-rich genetic makeup. The composition fits well in the range observed for other xenacolomorphs (43% GC content in X. bocki (Schiffer et al 2022), or 39.1% GC content in P. naikaiensis (Arimoto et al 2019); all of them, also, enriched in A+T nucleotides.…”
Section: Discussionsupporting
confidence: 83%
“…In the assembled genomes of acoels, the content of repetitive sequences varies from a value of 53% in H. miamia to 61% in S. roscoffensis and the largest estimated value of 70% in P. naikaiensis . Moreover, in the related group of xenoturbellids, a recent sequencing project has revealed that the species X. bocki has a surprisingly low fraction of repeats, around 25% (Schiffer et al 2022). Interestingly, X. bocki also has a relatively compact genome of ~110 Mb (Schiffer et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GC content of S. roscoffensis genome is 36.7% ( Table 1 ), thus it is an AT-rich genome, similar to other xenacolomorphs [43% GC content in Xenoturbella bocki ( Schiffer et al 2022 ), 39.1% GC content in P. naikaiensis ( Arimoto et al 2019 )].…”
Section: Resultsmentioning
confidence: 96%